Genetic mechanisms underlying local spontaneous brain activity in episodic migraine - Gui, Wei; Lu, Fengqing; Fu, Lulan; Deng, Ziru; Zhao, Xiuxiu; Cheng, Wenwen; Yang, Ying; Wang, Yu (Frontiers in Neuroscience, 2024)
Advances in neuroimaging techniques during the past few decades have captured impaired functional brain activity in migraine disorders, yet the molecular mechanisms accounting for its alterations in migraine remain largely unknown. 27 patients with episodic migraine (EM) and 30 matched healthy controls (HCs) underwent resting-state functional and structural magnetic resonance imaging (MRI) scans. Regional homogeneity (ReHo), low-frequency fluctuations (ALFF), fractional amplitude of low-frequency fluctuations (fALFF) of fMRI were compared between the two groups. Based on Allen Human Brain Atlas and risk genes in migraine, we identified gene expression profiles associated with ReHo alterations in EM. Compared with HCs, patients with EM showed increased ReHo in the left orbital part of superior frontal gyrus (P < 0.05, cluster-level FWE-corrected). The expression profiles of 16 genes were significantly correlated with ReHo alterations in EM (P < 0.05/5,013, Bonferroni corrected). These genes were mainly enriched for transcription regulation, synaptic transmission, energy metabolism as well as migraine disorders. Furthermore, the neural activation was positively correlated with Hamilton Rating Scale for Anxiety (HAMA) scores. To testing the stability of our results, we repeated our procedure by using ALFF and fALFF, and found these results had a high degree of consistency. Overall, these findings not only demonstrated that the regional brain activity was increased in patients with EM, which was associated with emotional regulation, but also provided new insights into the genetic mechanisms underlying these changes in migraine.